POTENSI METODE MICROBIAL FUEL CELL DUAL CHAMBER TERHADAP PENURUNAN KANDUNGAN BAHAN ORGANIK DAN PRODUKSI LISTRIK PADA LIMBAH CAIR TAHU - Muhammad Busyairi (Teknologi Sipil : Jurnal Ilmu Pengetahuan dan Teknologi, 2018)
Tofu industry has become one of the most widespread home industries. In the production process, the tofu industry produces liquid and solid waste can cause environmental pollution, especially the aquatic environment. Microbial Fuel Cell method (MFC) is a waste treatment method by utilizing microbial activity to minimize waste while producing electricity The purpose of this research is to know the effectiveness of MFC in reducing organic matter in tofu wastewater, and the amount of electric energy generated. The reactor used is a type of MFC dual chamber. KMnO4 was used at the cathode space and tofu wastewater in the anode chamber. The electrodes used are graphite type carbon. Performed COD measurements every 12 hours, while for the current strength and voltage is measured every 6 hours during the operating time of 48 hours. The results showed that dual chamber MFC method can decrease dissolved organic matter and produce electricity. The optimum efficiency of COD was decreased 42,86% and efficiency of BOD decrease 86,83% at 48 hours. As for the maximum electricity production of 28.61 mW / cm2 at the residence of 24 hours.